Onomastic space in the «Tarikh-i Rashidi». (Journal of Oriental Studies, 2016)
The article examines toponyms in «Tarikh-i Rashidi» written by Muhammad Haidar, in the Middle Ages and has great significance for the history of the Kazakhs and Kazakhstan. Work consists of two Defters.
Keywords: «Tarih-i Rashidi»; toponyms; plavename; onomastic; Muhammad Haidar